Clinical presentation of paediatric patients with COVID-19 admitted to a single paediatric intensive care unit (PICU) in Iran - Saeed, Amir (BMJ Paediatr Open, 2020)
OBJECTIVES: To describe the clinical characteristics of paediatric patients admitted to a single paediatric intensive care unit (PICU) in Iran with COVID-19. METHODS: A cross-sectional study of paediatric patients who were admitted to a COVID-19-dedicated PICU from 16 March 2020 to 21 April 2020 with COVID-19. RESULTS: Six children had confirmed COVID-19 and four had suspected COVID-19. Six had pre-existing chronic medical conditions. Nine had respiratory failure and needed ventilation. Five children, of whom four had chronic medical conditions, died. Four had cardiac arrhythmias. Clinical presentation included fever and cough. CONCLUSION: COVID-19 can be fatal in paediatric patients, especially in those with a chronic medical condition.